Review of the Implementation of Minimum Services for Loading Vehicles on Ships on the Bolok – Rote Route, East Nusa Tenggara Province - Sulistyorini, Erika Dwi; Pusriansyah, Ferdinand; Triwahyuni, Siti Nurlaili; Aziz, Dadang Abdul; Hatina, Damaida; Ramadhani, Shabrina (IWJ : Inland Waterways Journal, 2023)
The Minimum Service Standards for Ferry Transport are the minimum requirements that must be met by ferry transport companies in providing services to service users. Minimum Service Standards (SPM) inspection process so that when the ship operates it does not cause problems. However, in its implementation the Minimum Service Standards have not been implemented at the Bolok Ferry Port, especially for the Minimum Service Standards for Loading on 4 ships, namely: (1) KMP. Lakaan; (2) KMP. Skipjack II; (3) KMP. Uma Kalada; and (4) KMP. Inerie II on the Bolok – Rote route. The aim of this research is to determine the level or percentage of compliance with the Minimum Service Standards for Loading vehicles on 4 ships on the Bolok – Rote Route. The method used is an observation method in the form of a survey of the distance between vehicles and the level of conformity to Minister of Transportation Regulation Number 62 of 2019 concerning Minimum Service Standards for Ferry Transport. Based on the results of the analysis, it can be seen that on 4 (four) ships in The Bolok – Rote route does not comply with Ministerial Regulation Number 62 of 2019 concerning Minimum Service Standards (SPM) for Ferry Transport, namely: (1) KMP. The conformity rate was 62%; (2) KMP. Cakalang II conformity level of 62%; (3) KMP. Uma Kalada's conformity rate was 65.5%; and (4) KMP. Inerie II conformity rate is 65.5%. Based on the analysis, ship operators can increase the Minimum Service Standards (SPM) for vehicle loading, especially in the following aspects: (1) Safety aspects require improvements to sprinklers and smoke detectors; (2) Security aspects that require providing CCTV on the card deck and regulating the distance between vehicles; and (3) Convenience/affordability aspects include changes to the cardeck height, improvements to lights and fastening to the vehicle when sailing.